A real-world analysis of cardiac rupture on incidence, risk factors and in-hospital outcomes in 4190 ST-elevation myocardial infarction patients from 2004 to 2015. Issue 5 (August 2020) - Hao, Ziyong; Ma, Jun; Dai, Jinjie; Shao, Qin; Shen, Lan; He, Ben; Jiang, Lisheng
Abstract : Background: Cardiac rupture is a disastrous but uncommon complication of acute ST-elevation myocardial infarction (STEMI). The incidence, risk factors and in-hospital outcomes related to cardiac rupture in the current era are unknown. Methods: This study consecutively collected all acute STEMI patients admitted to a single tertiary center in China from January 2004 to December 2015. Characteristics of each cardiac rupture were collected and analyzed. Results: Among 4190 patients, 75 (1.8%) patients had cardiac rupture, including 33 at the ventricular septum and 42 at the left ventricle free wall (LVFW). Patients with cardiac rupture were more likely to be female, with more advanced age, lower rate of primary percutaneous coronary intervention (PPCI), and higher in-hospital mortality. Compared with survivors, the death cases were older, had a higher white blood cell count, higher rate of delayed admission (>12 h from symptom onset to door), earlier occurrence of cardiac rupture, higher percentage of LVFW rupture and lower rate of surgical repair. Logistic regression analysis showed that surgical repair served as the most valuable factor affecting survival. Moreover, elevated white blood cell count and advanced age might be related to an increased in-hospital death due to cardiac rupture. Conclusions: In this contemporary cohort, female sex, advanced age and low rate of PPCI post-STEMI are associated with an increased risk of cardiac rupture. Advanced age and elevated white blood cell count might be related to an increased in-hospital mortality after cardiac rupture, whereas surgical repair served as the most valuable factor affecting survival.